Radio empire : the BBC's Eastern Service and the emergence of the global anglophone novel - Morse, Daniel Ryan (Modernist latitudes., 2020)
"The BBC's Empire Service was a cauldron of global modernism. James Joyce's Finnegan's Wake found an audience among radio listeners in India, while C. L. R. James read his anticolonial novel The Black Jacobins to listeners throughout the British empire. Writers tested aesthetics, audience, and form before Empire Service microphones, broadcasting these experiments to the colonies before they were made available in England. Rather than spreading imperial views to peripheral colonies, as prevailing scholarship has argued, the BBC in Radio Empire is a contact zone and site of experimentation and contestation. Modernist writers did not simply prop up the empire. Instead, the need to appeal to discerning, well-educated listeners at the edges of the empire pushed the boundaries of literary work in London, inspired high-cultural broadcasting in England, and formed an invisible but influential global cultural network. Morse analyzes how radio's instantaneity and global reach were instrumental in imagining cultural relations during, after, and against imperialism. Far from a monolithic entity, the BBC offers a wide variety of responses to various modernities. The book brings original archival research to bear on the burgeoning scholarly interest in global modernism. Drawing examples from broadcasting by Indian, Nigerian, Irish, Trinidadian, and English writers such as Joyce, James, Forster, Mulk Raj Anand, Attia Hosain, Venu Chitale, and Wole Soyinka, this book expands our knowledge of broadcasting outside of Western Europe and demonstrates the ways in which the BBC Empire Service offers a new understanding of the relationship between colonial center and periphery and how the radio service often undermined the British imperial world view. By reading unpublished radio scripts from the BBC's archives alongside novels, Morse offers a compelling interdisciplinary argument to understand the development of Global Anglophone culture"--